Expression of PTEN‐long mediated by CRISPR/Cas9 can repress U87 cell proliferation. Issue 12 (19th June 2017) - Fang, Na; Gu, Tingxuan; Wang, Yahui; Wang, Shuzhen; Wang, Fengling; An, Yang; Wei, Wenqiang; Zhang, Weijuan; Guo, Xiangqian; Nazarali, Adil J; Ji, Shaoping
Abstract: PTEN is a tumour suppressor that is frequently mutated in a variety of cancers. Hence, PTEN has significant potential as a therapeutic molecule. PTEN‐long is an alternative translation variant, with an additional 173 amino acids added to the N‐terminal of the canonical PTEN when CUG of the mRNA is utilized as the start codon. PTEN‐long is secreted into serum and can re‐enter cells throughout the body. One of the major barriers for gene therapy is to efficiently and specifically deliver DNA or RNA material to target cells. As an alternative approach, if a therapeutic protein can be directly delivered to target cell of interest, it should theoretically function well within the cells, particularly for genes that are deficiently expressed in vivo . Most therapeutic proteins are incapable of efficiently permeating the cell membrane. In this study, we have employed CRISPR/Cas9 gene editing tool combined with single‐stranded template to edit CTG of PTEN‐long to ATG in the genome. Two guide RNAs close to CTG site were found to have similar efficiency in driving PTEN‐long expression. Furthermore, we detected PTEN‐long expression in transfected whole‐cell lysate and in concentrated culture media in Western blot. Interestingly, the culture media of PTEN‐long expression can reduce Akt phosphorylation level and repress U87 cell proliferation compared to wild‐type U87 or control media. Taken together, PTEN‐long driven by CRISPR/Cas9 imports and exports cells and represses nearby cell proliferation, indicating the PTEN‐long generated by CRISPR/Cas9 has potential to be an alternative strategy for PTEN gene therapy.